Intergenerational transfers and private savings: an experimental study. - Heijden, Eline C. M. van der; Nelissen, Jan H. M.; Potters, Jan J. M. (Kyklos, 1997)
An overlapping-generations experiment was conducted to examine the individual preference between intergenerational transfers and savings. Findings indicated that if savings can be made, individuals decide to gradually opt out of the intergenerational transfer system. In that case, the mean individual pay-offs are reduced but their apportionment among individuals is less erratic, indicating that the risk aversion is a primary cause of the decline of intergenerational transfers. The eagerness to provide for previous generations does not disappear totally, but the amount of solidarity between successive generations, assessed by the correlation between current and past transfers, does not decrease significantly following the introduction of the savings option.